2002
DOI: 10.1002/etc.5620211113
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic uptake of bioavailable cadmium, selenium, and zinc by Daphnia magna

Abstract: Kinetic uptake of Cd, Se(IV), and Zn by Daphnia magna from the dissolved phase was determined using radiotracer techniques in moderately hard water. The metal influx rate and distribution in the soft tissue and the exoskeleton of the daphnids as influenced by metal concentration, inorganic ligands including pH, Ca2+ and SO4(2-), and body size were quantified. When the metal concentrations were <180 nM for Cd and <769 nM for Zn, the concentration factor in daphnids increased linearly within the 12 h of exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(10 citation statements)
references
References 47 publications
3
5
2
Order By: Relevance
“…The increased sensitivity was attributed to larger area/volume ratios, which led to a size-dependent uptake and higher metabolic rates of younger organisms. Similar findings were observed by Yu and Wang [ 57 ], Hutchinson et al [ 58 ], and Stuhlbacher et al [ 59 ]. The response to a stressor can be affected by an organism’s physiological state.…”
Section: Resultssupporting
confidence: 90%
“…The increased sensitivity was attributed to larger area/volume ratios, which led to a size-dependent uptake and higher metabolic rates of younger organisms. Similar findings were observed by Yu and Wang [ 57 ], Hutchinson et al [ 58 ], and Stuhlbacher et al [ 59 ]. The response to a stressor can be affected by an organism’s physiological state.…”
Section: Resultssupporting
confidence: 90%
“…A slight decrease in molts was observed with higher FPW concentrations; however, this trend was not significant (Figure B; p = 0.250). Overall, these results are similar to previous work in Daphnia exposed to FPW for 21 days. , Neonate Daphnia are more sensitive than their adult counterparts, due to their high mass-specific metabolic rate and higher surface area to volume ratio, increasing the potential contact points for transport across the epithelium . Previous studies showed that neonate Daphnia had lower survival, neonate production, and first brood size to metal stressors than 7 days adult Daphnia , and that LC50s for FPW were vastly lower in neonates (0.19%) than in adults (7 days old) Daphnia (0.75%) .…”
Section: Resultssupporting
confidence: 88%
“…22,32 Neonate Daphnia are more sensitive than their adult counterparts, due to their high mass-specific metabolic rate and higher surface area to volume ratio, increasing the potential contact points for transport across the epithelium. 71 Previous studies showed that neonate Daphnia had lower survival, neonate production, and first brood size to metal stressors than 7 days adult Daphnia, 72 and that LC50s for FPW were vastly lower in neonates (0.19%) than in adults (7 days old) Daphnia (0.75%). 32 The observed changes to reproduction are unsurprising considering the high mortality observed in each FPW sample.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…Liver is probably the main receptor of zinc in summer, when the amount of ingested metals from diet originates mainly from larvae of midges (Pastorino et al 2020c ). Chironomidae have high concentrations of zinc probably because of their inefficient efflux rates or detoxification mechanisms, as reported in some other studies on aquatic invertebrates (Yu and Wang 2002 ). Compared to other fish species, bullheads seem to prefer water with relatively higher zinc content (Andreji and Dvorak 2018 ).…”
Section: Discussionsupporting
confidence: 55%